Breaks: Travesti painting as an act of (re)existence in the Amazon of Pará (Palíndromo, 2026)
This article examines the series of paintings Quebras, by travesti artist Rafael Matheus Moreira, as an act of (re)existence in the Amazon region of Pará. The artistic production in question challenges the Western canon by re-signifying classical painting genres, placing travesti bodies as protagonists, in contrast to historically fetishized or marginalized representations. Inspired by the popular movement Raio que o Parta, which used broken tile fragments to create modernist facades, the artist employs the metaphor of the “break” to symbolize the deconstruction of cisgender gazes and the reconstruction of travesti identities through art. The study aims to reflect on painting as a political gesture of insurgency and celebration of trans existence, addressing themes such as collective memory, resistance, and the subversion of hegemonic narratives. Methodologically, the research is grounded in an autobiographical and ethnographic approach, articulating theoretical references from queer art, gender studies, and social memory. The results highlight that the artist’s trajectory and institutional recognition — with exhibitions in venues such as MASP and awards like the Arte Pará — constitute fissures in the normative art system, affirming painting as a practice of healing, recording, and re-existence. It is concluded that the Quebras series functions as a visual and affective archive, opening spaces for the visibility and reinvention of possible futures for trans people in the Amazon and beyond.
Keywords: contemporary art; painting; travestis; gender identity; brazilian amazon